Faktor-Faktor Yang Mempengaruhi Kunjungan Wisatawan ke Air Terjun Simbilulu Kabupaten Pakpak Bharat Sumatera Utara - Feronika Berutu (Departemen Pariwisata Universitas Negeri Padang, 2023)
Pakpak Bharat Regency has natural resources that can be managed and generate economic value for the welfare of the people in the district, one of which is in the field of tourism. There are several tourism destinations in this district, one of which is the Simbilulu waterfall, which is a destination that is the focus of the government in its development, in increasing tourist visits there are several things that need attention. Attractiveness, Accessibility and Facilities are elements that are factors of the success of a tourist destination. These elements are factors for consideration by tourists in visiting destinations. Simbilulu Waterfall tourism destinations have started well, but there are still some that do not meet the needs of tourists when visiting destinations. If this destination is developed and managed optimally, it is likely that it will also have a positive impact on the community around the tourist destination. This study examines how much influence the variables of Attractiveness, Accessibility and Facilities have on tourist visits to Simbilulu Waterfall, Pakpak Bharat Regency, North Sumatra. The population in this study are tourists who come to visit the Simbilulu waterfall with an average value per month. The minimum sample in this study is based on the Slovin formula of 95 respondents with an error rate of 10%, using the incidental sampling technique. Data analysis with multiple linear regression, coefficient of determination and hypothesis. Results of the study showed that Attraction contributed 45.3%, Accessibility 7.1%, and Facilities 14.3%, to tourist visits to Simbilulu Waterfall. The hypothesis shows that there is an influence between the variables of attractiveness and facilities is accepted, while the hypothesis that there is an effect of accessibility is rejected.